Cardiac Specific Effects of Thyroid Hormone Analogues - Danzi, S.; Klein, I. (Hormone and Metabolic Research, 2011)
There is significant interest in development of thyroid hormone analogues to harness specific properties as therapeutic agents for a variety of clinical indications including obesity, hypercholesterolemia, heart failure, and thyrotoxicosis. To date, most analogues have been designed to target liver specific effects, which can promote weight loss and lipid lowering through either tissue specific uptake or thyroid hormone receptor (TR) β isoform selectivity at the same time minimizing the unwanted cardiac and bone effects. We have developed a molecular biomarker assay to study the induction of the transcription of the cardiac specific α-myosin heavy chain (MHC) gene as a more sensitive and specific measure of thyroid hormone action on cardiac myocytes. We tested 5 TRβ and 1 TRα selective agonists as well as 2 putative TR antagonists in our α-MHC hnRNA assay. Using reverse transcription and polymerase chain reaction, we measured the induction of the α-MHC primary transcript in response to administration of drug. The TRα and only 2 of the TRβ agonists were highly active, when compared to the effect of T3, at the level of the cardiac myocyte. In addition, our data suggests that the reason that the antagonist NH-3 is not able to block the T3-mediated induction of α-MHC is that it does not get transported into the cardiac myocyte. Our data suggest that this assay will be useful in preclinical studies of the potential cardiac specific effects of thyroid hormone analogues and that predictions of function based on structure are not necessarily accurate or complete.
Keywords: analogue; heart; T3; T4; triiodothyronine